Analisis Multiple Intelligence dalam Pembelajaran Biologi - Fuadiyah, Sadiatul; Sriyati, Siti; Kumalasari, Lita; Melta, Defrian (Pedagogi Hayati, 2022)
Multiple intelligence theory can be used as a basis for assessing children's intelligence potential, the results or multiple intelligence profiles will be very useful for guidance and education. The challenges of era 4.0 and the characteristics of today's generation of learners encourage teachers to be able to innovate and develop the learning process continuously. One of the innovations that can be carried out is the implementation of multiple intelligence-based learning. For this reason, it is necessary to know the multiple intelligences that can be accommodated in learning biology on cell material. This research is a descriptive narrative research. The sample taken was total sampling using subjects as many as 7 grade 8 students and 1 science teacher. The research was conducted at Equal Bright School Bandung because this school is based on multiple intelligence in its learning. Data collection techniques were conducted by direct observation techniques to see the implementation of biology learning, interview sheets to describe learning from teachers and students, documentation in the form of photos and videos and multiple intelligence inventory questionnaire adapted from McKenzie (1999). The data collected from the analysis of lesson plans, interviews and multiple intelligence questionnaires were analyzed using descriptive methods, the calculations carried out in the form of categorization.  The results of the research show that the teachers' learning of the biology of the cells can facilitate several multiple intelligences, kinesthetic, naturalistic, interpersonal, visual-spatial, verbal and intrapersonal. The creation of a biology learning plan based on multiple intelligence and learning in the classroom is based on the dominant intelligence of the student.